Clinical Significance of Detection of Peripheral Blood VASP Level in Lung Cancer Patients. (31st July 2022) - Ma, Jin; Zhu, Shumin; Chen, Zhiqing; Li, Xinyuan; Mao, Yafei; Tian, Xin; Zhao, Li; Li, Yanming; Li, Baoqin; Geng, Yulan
Abstract : This paper explores the relationship between the clinical value of vasodilator-stimulated phosphoprotein (VASP) in lung cancer tissue and its diagnosis and severity. Totally 100 patients who were clinically diagnosed with lung cancer from January 2018 to December 2020 were enrolled in our study. They were assigned into two groups according to the presence of lymph node metastasis. The VASP levels were measured by flow cytometry. The correlation between the expression of VASP in tumor tissue and the clinical characteristics and prognosis in patients was analyzed. The diagnostic efficacy of plasma VASP with squamous cell carcinoma antigen (SCC), neuron-specific enolase (NSE), cytokeratin-19 fragment (CYFRA21-1), prosecretin-releasing peptide (proGRP), and lung cancer was analyzed. The results were compared with APACHE III score to evaluate the accuracy of VASP in determining the severity of patients. This paper finds that the value of VASP in the non-lymph node metastasis group was significantly higher than that in the healthy control group, and the VASP level in the lymph node metastasis group was significantly higher than that in the non-lymph node metastasis group and the healthy control group (all p values <0.05). The APACHE III score of the lymph node metastasis group was higher than that of the non-lymph node metastasis group (p value <0.05). The diagnostic efficacy of VASP is similar to that of SCC, NSE, CYFRA21-1, and proGRP. The plasma VASP value was statistically different in the survival group and the death group, with higher level observed in the death group compared to survival group (all p values <0.05). The value of plasma VASP alone and acute physiology and chronic health evaluations III (APACHE III) score for lung cancer mortality was similar (47.06% vs. 52.94%, p value >0.05). Similar accuracy was observed in VASP and APACHE III score in predicting mortality of lung cancer (84.37% vs. 85.77%, p value>0.05). This paper concludes that the level of VASP correlates to the severity of the lung cancer and survival of the patients.